Glutamate and GABA Homeostasis and Neurometabolism in Major Depressive Disorder - Sarawagi, Ajay; Soni, Narayan Datt; Patel, Anant Bahadur (Frontiers in Psychiatry, 2021)
Major depressive disorder (MDD) is a leading cause of distress, disability and suicidality. As per latest WHO report, MMD is affecting more than 260 million people with severe economic burden worldwide. Despite, huge investment of many decades in research, the underlying pathophysiology and etiology is not fully understood. Glutamate and -aminobutyric acid (GABA) are the major excitatory and inhibitory neurotransmitters, respectively, in the matured central nervous system. Imbalance in the levels of these neurotransmitters have been implicated in different neurological disorders. Nuclear Magnetic Resonance (NMR) Spectroscopy is the only non-invasive method to study the neurometabolite homeostasis. Moreover, 13C NMR spectroscopy together with an intravenous administration of non-radioactive 13C labeled glucose or acetate provides a measure of cellular energetics and neurotransmitter cycling in vivo. In this article, we will provide an introduction to neurotransmitter cycling, and NMR based measurement of neurometabolite levels and neurometabolism in brain. This will be followed by a comprehensive review of glutamate and GABA homeostasis, neuronal and astrocytic energetics in different brain regions under depression. Finally, we will provide recent advancement in the treatment approaches of depression that are targeted to Glutamate and/or GABA pathways.